Agroecological approaches to enhance pollination services in horticultural crops - Srivastava, Swapnil (Horticultural Biotechnology Research, 2024)
Pollination is a crucial ecosystem service that directly influences the yield and quality of horticultural crops. However, the decline in pollinator populations due to factors such as habitat loss, pesticide use, and climate change poses significant risks to agricultural productivity. This paper reviews agroecological approaches to enhancing pollination services in horticultural crops, focusing on strategies that promote biodiversity, create pollinator-friendly habitats, and minimize environmental stressors. By implementing practices such as diversified cropping systems, organic farming, and the conservation of natural habitats, agroecology provides sustainable solutions to support pollinator health and ensure the resilience of horticultural production systems. The review also examines the benefits and challenges of these approaches and suggests future research directions to optimize pollination services in horticulture.